Investigation of asphalt texture roughness on friction evolution for wheeled vehicles. Issue 2 (2nd April 2016) - Raslavičius, Laurencas; Pakalnis, Algis; Keršys, Artūras; Skvireckas, Ramūnas; Juodvalkis, Darius
Abstract: Novelty of the research lies in understanding the safety advantages of asphalt made using advanced pavement design process – compact asphalt pavement installation. Variation of tyre–road friction coefficient for this type of pavement design is new and little-studied phenomenon. The present study focuses on the research into tyre–pavement interaction on dry asphalt pavement surfaces to quantify the effect of microprofile on vehicle performance in establishing its braking conditions. The data on a number of different indications (vehicle speed, adhesion coefficients calculated on the basis of braking and friction forces, maximum adhesion coefficient mmax and its 'minimum' value m100% ) and measurement results generated using SRT-4 device for investigation of two road stretches at intervals of 100 m are presented in this paper. The interdependence analysis of statistical variables mmax and m100% has also been presented to exhibit the use of the method. Following statistical parameters are taken into account during random value analysis in order to assess the homogeneity of data: average value, dispersion, standard deviation, confidence interval around a sample mean, and correlation function. Finally, we provide a map between the adhesion coefficient and the longitudinal slip rate for stable and unstable braking conditions of a vehicle.